Efektivitas Penggunaan Aplikasi Zoom Sebagai Sarana Pembelajaran Daring Selama Pandemi Covid 19 - Rahma Krisna Ulfah; Fenina Niken Pratiwi; Ivan Hadiananta; Sonia Nursa Putri; Veni Febria Emza; Jeni Wardi (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2021)
Abstract Online learning is a learning method that is currently being actively developed by every teacher and educator. This learning method is a solution for the limited learning activities during the Covid 19 pandemic as it is today. This research is motivated by the application of social distancing which requires students to carry out online learning activities in order to prevent the transmission of COVID-19. The purpose of this study is to determine the effectiveness of the Zoom Meeting application used by students in distance learning during the COVID-19 pandemic. The effectiveness of online learning really needs to be considered so that students understand when learning is taking place. This study has a sample of 46 respondents who are students of the Faculty of Economics, Lancang Kuning University consisting of 31 female students (67.4%) and 15 male students (32.6%) who come from the management study program totaling 31 students (67, 4%), and from the accounting study program there were 15 students (32.6%). The data retrieval technique that we apply is to use Google Forms. We use the google form to distribute questionnaires, the use of this google form is because the google form is more effective, fast and broad to distribute questionnaires to subjects, on the other hand because it is still in a pandemic condition and there is also a policy from the government to stay home or social distancing so we cannot use the direct interview method. The research subjects were students of the Faculty of Economics, Lancing Kuning Universities. This study was conducted to determine the effectiveness of the use of the Zoom Meeting platform by the Faculty of Economics, Lancing Kuning University during the COVID-19 pandemic. Abstrak Pembelajaran melalui daring merupakan metode pembelajaran yang saat ini aktif dikembangkan oleh setiap tenaga pengajar dan pendidik. Metode pembelajaran ini menjadi sebuah solusi bagi terbatasnya kegiatan pembelajaran dimasa pandemi Covid 19 seperti saat ini. Penelitian ini dilatar belakangi adanya penerapan social distancing yang mengharuskan mahasiswa melaksanakan kegiatan pembelajaran secara online dalam rangka mencegah penularan COVID-19. Tujuan penelitian ini yaitu mengetahui efektivitas aplikasi Zoom Meeting yang digunakan mahasiswa dalam pembelajaran jarak jauh pada masa pandemi COVID-19. Efektivitas pembelajaran online sangat perlu diperhatikan agar mahasiswa memahami saat pembelajaran berlangsung. Penelitian ini memiliki sampel 46 responden yang merupakan mahasiswa Fakultas Ekonomi Universitas Lancang Kuning yang terdiri atas 31 mahasiswi perempuan (67,4%) dan 15 mahasiswa laki-laki (32,6%) yang berasal dari prodi manajemen yang berjumlah 31 mahasiswa (67,4%), dan dari prodi akuntansi berjumlah 15 mahasiswa (32,6%). Teknik pengambilan data yang kami terapkan adalah menggunakan google form. Kami menggunakan google form untuk menyebarkan kuesioner, penggunaan google form ini dikarenakan google form lebih efektif, cepat dan luas untuk menyebarkan kuesioner kepada subjek, di sisi lain karena masih dalam kondisi pandemi dan juga adanya kebijakan dari pemerintah untuk tetap dirumah atau stay home dan social distancing maka kami tidak dapat menggunakan metode wawancara secara langsung. Subjek penelitian adalah mahasiswa Fakultas Ekonomi Universities Lancing Kuning. Penelitian ini dilaksanakan untuk mengetahui efektivitas pemanfaatan platform Zoom Meeting oleh Fakultas Ekonomi Universitas Lancing Kuning pada masa pandemi COVID-19.